2013
DOI: 10.1558/sols.v6i3.491
|View full text |Cite
|
Sign up to set email alerts
|

When 'Sir' and 'Madam are not: Address terms and reference terms students use for faculty in a Ghanaian university

Abstract: Address terms and reference terms are common but key naming behaviours that are enacted in various social interactions. Thus, unsurprisingly, they have received much attention in sociolinguistic research since the 1960s. The use of these two communicative acts in the academic setting, however, seems under-researched. This study, therefore, investigated address terms and reference terms students used for faculty in a public university in Ghana, utilizing Scott’s (1990) sociological theory on resistance to domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…We believe that many significant aspects of address still remain to be uncovered, in particular the possible degree and nature of variability within the same national variety due to such factors as regional identity, area of study, size of universities, and so forth. At the same time, an additional fruitful area for future research may be, for instance, the description of address practices in non-dominant varieties of English, such as the "world Englishes" (Kachru 1997) spoken in countries with English-colonial heritage in Africa and Asia (see for example Afful and Mwinlaaru 2012), or the address strategies employed in academic settings where English is adopted as a lingua franca (Formentelli 2009b: 235). The contact between English and local languages and cultures, as well as the kaleidoscope of speakers' linguistic and cultural backgrounds typical of these contexts of interaction are very likely to give rise to fascinating patterns of address that need to be documented in order to enrich our understanding of how different styles of address in English shape human relations on a global scale.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that many significant aspects of address still remain to be uncovered, in particular the possible degree and nature of variability within the same national variety due to such factors as regional identity, area of study, size of universities, and so forth. At the same time, an additional fruitful area for future research may be, for instance, the description of address practices in non-dominant varieties of English, such as the "world Englishes" (Kachru 1997) spoken in countries with English-colonial heritage in Africa and Asia (see for example Afful and Mwinlaaru 2012), or the address strategies employed in academic settings where English is adopted as a lingua franca (Formentelli 2009b: 235). The contact between English and local languages and cultures, as well as the kaleidoscope of speakers' linguistic and cultural backgrounds typical of these contexts of interaction are very likely to give rise to fascinating patterns of address that need to be documented in order to enrich our understanding of how different styles of address in English shape human relations on a global scale.…”
Section: Discussionmentioning
confidence: 99%
“…It seems therefore crucial that people engaged in tertiary education be aware of the address options at their disposal and the appropriate combinations of forms to be used to avoid social sanction. Recent studies have confirmed the importance of appropriate address in marking power and distance in higher education across languages and varieties of the same language (for example, among others, Formentelli, 2009;Afful and Mwinlaaru, 2012;Merrison, Wilson, Davies and Haugh, 2012;Formentelli and Hajek, 2013;Chejnová, 2014;Burt, 2015). However, despite the increasing global importance of higher education, research in this area is still very limited for most languages, including Italian.…”
Section: Introductionmentioning
confidence: 91%
“…The use of first names to address people generally reduces the interpersonal relationships between people (Formentelli, 2009;Afful & Mwinlaaru, 2012). Thus students avoid these awkward feelings and go for the more formal one while lectures, go for the informal ones.…”
Section: Addressing Students By Lecturersmentioning
confidence: 99%
“…dress terms. That is, students often used Title (T)/Last Name (LN) as address terms generally for faculty members and First Name (FN) minimally as a reference term or what he describes as usage in "delayed time" Afful and Mwinlaaru (2012). focused on the address and reference terms students used for faculty members in a Ghanaian University context.…”
mentioning
confidence: 99%